A Bornean peat swamp forest is a net source of carbon dioxide to the atmosphere. (27th September 2020) - Tang, Angela C. I.; Melling, Lulie; Stoy, Paul C.; Musin, Kevin K.; Aeries, Edward B.; Waili, Joseph W.; Shimizu, Mariko; Poulter, Benjamin; Hirata, Ryuichi
Abstract: Tropical peat forests are a globally important reservoir of carbon, but little is known about CO2 exchange on an annual basis. We measured CO2 exchange between the atmosphere and tropical peat swamp forest in Sarawak, Malaysia using the eddy covariance technique over 4 years from 2011 to 2014. The CO2 fluxes varied between seasons and years. A small carbon uptake took place during the rainy season at the beginning of 2011, while a substantial net efflux of >600 g C/m 2 occurred over a 2 month period in the middle of the dry season. Conversely, the peat ecosystem was a source of carbon during both the dry and rainy seasons in subsequent years and more carbon was lost during the rainy season relative to the dry season. Our results demonstrate that the forest was a net source of CO2 to the atmosphere during every year of measurement with annual efflux ranging from 183 to 632 g C m −2  year −1, noting that annual flux values were sensitive to gap filling methodology. This is in contrast to the typical view of tropical peat forests which must have acted as net C sinks over time scales of centuries to millennia to create the peat deposits. Path analyses revealed that the gross primary productivity (GPP) and ecosystem respiration (RE) were primarily affected by vapour pressure deficit (VPD). Results suggest that future increases in VPD could further reduce the C sink strength and result in additional net CO2 losses from this tropical peat swamp forest in the absence of plant acclimation to such changes in atmospheric dryness. Abstract : The annual course of cumulative net ecosystem CO2 exchange exhibited different responses to climatic and hydrologic variability during the four‐year observation period. The forest was a net carbon sink from January until the middle of the dry season in June 2011, after which increasing RE and declining gross primary productivity (GPP) resulted in a large carbon loss event of >600 g/m 2 over a 2‐month period. GPP was more sensitive to environmental variability and exhibited greater interannual variability than RE.